TEACHING ENGLISH FOR ISLAMIC BUSINESS MANAGEMENT PROGRAMS: ENHANCING LANGUAGE SKILLS FOR FUTURE LEADERS - Candraning Prawerti, Ringgi (CV. Lafadz Jaya, 2024)
The teaching of English in Islamic Business Management programs plays a vital role in preparing students for the global marketplace. As English becomes increasingly important in business communication, the need for effective language instruction tailored to the specific context of Islamic business practices is essential. This paper explores the methodologies and approaches to teaching English to students in Islamic Business Management programs. It highlights the significance of integrating business terminology, Islamic principles, and communication skills into the curriculum. Through qualitative research, including interviews with educators and observations of classroom practices, the study identifies effective strategies for enhancing students' English proficiency while ensuring alignment with Islamic business ethics. The findings indicate that contextualized learning, interactive activities, and the use of authentic materials significantly improve students' language skills and their understanding of business concepts. Challenges such as limited resources and varying levels of student proficiency are discussed, along with recommendations for future curriculum development. Ultimately, this study emphasizes the importance of a comprehensive English language program that equips students with the necessary skills to excel in the field of Islamic business.